Internalization of Character and Critical Thinking in Elementary School Students through Traditional Games - Susanto (Kilau Publishing, 2025)
Instilling character values and critical thinking skills in elementary school students is an important focus in 21st century learning. One contextual approach that can be utilized is through traditional games, which are rich in educational, collaborative, and social elements. This study aims to review various literature discussing the role of traditional games in internalizing character values and developing critical thinking skills in elementary school students. The method used is a systematic literature review of relevant national and international articles over the past ten years. The results of the study indicate that traditional games positively contribute to the formation of values such as honesty, responsibility, cooperation, and sportsmanship. Additionally, activities within games that involve decision-making, problem-solving, and team strategies can stimulate critical thinking skills in children from an early age. This study recommends integrating traditional games into the elementary school curriculum as an effective culture-based learning tool for simultaneously shaping students' character and cognitive abilities.